Lectotypification of the name Striga densiflora (Orobanchaceae) - Moolayil, Omalsree; Arjunan, Sujana K; Sreenivas, Vadakkekara (Phytotaxa, 2018)
The genus Striga Loureiro (1790: 22) belongs to the family Orobanchaceae and comprises about 43 species (Omalsree et al. 2015) with the highest diversity in tropical Africa, where 28 taxa have been recorded and 22 of them are endemic (Mohamed et al. 2001, Fischer et al. 2011). In India, ten species were recorded so far including four recently described species, viz. Striga kamalii Omalsree et al. (2015: 166), S. indica Prabhu et al. (2013: 284), S. musselmanii Omalsree & V.K. Sreenivas (2018a: 99) and S. scottiana Jeeva et al. (2012: 79). Very limited information is available on the genus in India except some sketchy enumerations in the state floras and few geographical distribution reports (Hooker 1884, Gamble & Fischer 1923, Saldanha 1963, Matthew 1981, Sasidharan 2013). The taxonomic position of less known Indian species as S. densiflora Bentham (1835: 41) Bentham (1836: 363), S. masuria (Buch.- Ham. ex Benth. 1835: 41) Benth, (1836: 364), S. sulphurea Dalzell & A. Gibson (1861: 182) etc. is still not clear. As a result, majority of specimens deposited in various herbaria are misidentified and plants are often referred to unresolved names (S. sulphurea) in databases (e.g. The Plant List 2018).